Pengembangan Interface dan Experience Aplikasi Manajemen Kegiatan Notelife Menggunakan Pendekatan Design Thinking.pdf - Ni Luh Gede Cahaya Putri Mahadewi; I Ketut Gede Suhartana (Informatics Department, Faculty of Mathematics and Natural Sciences, Udayana University, 2025)
The COVID-19 pandemic has presented major challenges to global productivity, especially for office workers who have switched to Work from Home (WFH). This research focuses on developing the